2019
DOI: 10.1186/s12935-019-0853-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and non-small cell lung cancer: new insights into signaling pathways

Abstract: Non-small-cell lung cancer (NSCLC) is a type of malignancy with progressive metastasis having poor prognosis and lowered survival resulting from late diagnosis. The therapeutic approaches for the treatment of this incurable cancer are chemo- and radiotherapy. Since current treatments are insufficient and because of drug-induced undesirable side effects and toxicities, alternate treatments are necessary and critical. The role of melatonin, produced in and released from the pineal gland, has been documented as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 92 publications
1
30
0
Order By: Relevance
“…apoptosis is a type of programmed cell death controlled by genes, including Bax and Bcl-2, that occurs as a homeostatic mechanism to maintain cell populations in the internal environment (11,29). Tumor cell studies have shown that melatonin can induce apoptosis (30); the present study demonstrated that early and late apoptotic rates of osteoblast cells treated with melatonin increased significantly as the concentration increased. The data also indicated that chromatin condensation in the nucleus and high expression of ParP-1 could be observed in osteoblast cells treated with 2 mM melatonin.…”
Section: Discussionsupporting
confidence: 52%
“…apoptosis is a type of programmed cell death controlled by genes, including Bax and Bcl-2, that occurs as a homeostatic mechanism to maintain cell populations in the internal environment (11,29). Tumor cell studies have shown that melatonin can induce apoptosis (30); the present study demonstrated that early and late apoptotic rates of osteoblast cells treated with melatonin increased significantly as the concentration increased. The data also indicated that chromatin condensation in the nucleus and high expression of ParP-1 could be observed in osteoblast cells treated with 2 mM melatonin.…”
Section: Discussionsupporting
confidence: 52%
“…Medical treatments to cure NSCLC are mainly surgery, radiation therapy, and chemotherapy (3). Radiation therapy combined with chemotherapy can produce a cure only in a small number of NSCLC patients because NSCLC is comparatively less sensitive to chemotherapy or radiation (4,5). Acquired resistance results in local tumor recurrence or failure of radiotherapy (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are the main source of reactive oxygen species (ROS) production and are a known target of melatonin [61,62]. As previously reported, melatonin presented a pro-oxidant effect in cancer cells [34][35][36]. A high concentration of ROS can damage mitochondrial and nuclear DNA and modify the expression of oncogenes and tumor suppressor genes [63,64].…”
Section: In Vitro Evidence Of Melatonin Effects Against Glioblastomamentioning
confidence: 91%
“…The antioxidant activity of melatonin is observed through the prevention of free radical formation, as well as the capacity to upregulate antioxidant enzyme activity and downregulate pro-oxidant enzymes [31][32][33]. Furthermore, in cancer cells, melatonin presents a paradoxical pro-oxidant effect, leading to cell death [34][35][36]. Therefore, melatonin may inhibit cancer development by increasing the induction of oxidative stress in tumor cells [37].…”
Section: Melatoninmentioning
confidence: 99%
See 1 more Smart Citation